The Influence Of Work Environment, Workload, Job Burnout, Job Satisfaction and Role Ambiguity on Employee Performance With Job Stress as A Mediating Variable - Yan Peres; Herry Maridjo (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to determine: (1) the direct effect of work environment on employee performance, (2) the direct effect of workload on employee performance, (3) the direct effect of job burnout on employee performance, (4) the direct effect of job satisfaction on employee performance, (5) the direct effect of role ambiguity on employee performance, (6) the effect of work environment on employee performance mediated by job stress, (7) the effect of workload on employee performance mediated by job stress, (8) the effect of job burnout on employee performance mediated by job stress, and (9) the effect of job satisfaction on employee performance mediated by job stress, and (10) the effect of role ambiguity on employee performance mediated by job stress. The sampling technique uses saturated sampling (census). The population of the study were employees who worked at the Badau Cross Border Post (PLBN) totaling 88 employees. Data were obtained by distributing questionnaires about work environment, workload, job burnout, job satisfaction, role ambiguity and job stress and employee performance to 88 respondents. Data analysis using Partial Least Square (PLS) and data processing using Smart PLS 3 software. The results showed that: (1) work environment directly has no effect on employee performance, (2) workload directly has no effect on employee performance, (3) job burnout directly has no effect on employee performance, (4) job satisfaction directly has a positive effect on employee performance, (5) role ambiguity directly has a negative effect on employee performance, (6) work environment has a positive effect on employee performance mediated by job stress (indirect-only full mediation), (7) workload negatively affects employee performance mediated by job stress (indirect-only full mediation), (8) job burnout has no effect on employee performance mediated by job stress (no-effect nonmediation), (9) job satisfaction has no effect on employee performance mediated by job stress (direct-only nonmediation), (10) role ambiguity has no effect on employee performance mediated by job stress (direct-only nonmediation.